Volume 5: Manufacturing Materials and Metallurgy; Ceramics; Structures and Dynamics; Controls, Diagnostics and Instrumentation; 1995
DOI: 10.1115/95-gt-308
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Shock Analysis and Testing of Simulated Ceramic Components for Gas Turbine Applications

Abstract: A ceramic gas seal for a utility gas turbine was designed and analyzed using ANSYS and CARES/LIFE. SN-88 silicon nitride was selected as the candidate material. The objective was to validate the failure prediction methodology using rectangular plates which were thermally shocked in a fluidized bed. The failure prediction methodology would then be applied to the representative component geometry. Refined ANSYS finite element modeling of both the plate and component geometries was undertaken. The CARES/LIFE reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
1999
1999

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Previous references to the creep and rupture of the silicon nitride of this study can be found in the literature. [15][16][17][18][19][20][21][22][23] The data from this study are part of a much larger engineering study of the suitability of monolithic silicon nitride for gas turbine engine applications. 24…”
Section: Introductionmentioning
confidence: 99%
“…Previous references to the creep and rupture of the silicon nitride of this study can be found in the literature. [15][16][17][18][19][20][21][22][23] The data from this study are part of a much larger engineering study of the suitability of monolithic silicon nitride for gas turbine engine applications. 24…”
Section: Introductionmentioning
confidence: 99%
“…The 7IS specimens were prepared by NGK and were machined in a direction parallel to the loading axis. The 71S flexure data from 90 tests were evaluated to estimate temperature-independent Weibull moduli and temperaturedependent Weibull scale parameters for two volume-distributed fracture origins, pores and large grains (Rajiyah et al, 1995).…”
Section: Sn-88 Strength Evaluationsmentioning
confidence: 99%
“…A life-limiting condition for ceramic gas turbine components is fast fracture during a full load turbine trip. An atmospheric thermal shock test rig was constructed for the purposes of proof test development and reliability model validation (Rajiyah et al, 1995). The rig consisted of an electric furnace, an air-fluidized bed of alumina particles and an elevator apparatus which rapidly transferred the specimen from r ",...""........"",...,…”
Section: Thermal Shock Reliability Modelmentioning
confidence: 99%
See 1 more Smart Citation